Pretreatment of Oil Palm Empty Fruit Bunch using Caustic Soda Solution for Lignin Isolation - Hidayat, Muslikhin; Aqilah, Nisrina Afifahtul; Winata, Adi (2022)
Oil palm empty fruit bunch (OPEFB) is lignocellulose consisting of cellulose, hemicellulose, and lignin. Lignin can be converted into derivative materials such as phenols, acetic acid, adhesives, surfactants, polymer products, and other chemical sources. This study was focused on extracting crude extract powder from OPEFB using NaOH solution. The correlation between processing time on yield and lignin content; and also, functional groups of the resulting lignin solids were analyzed. Delignification using NaOH was carried out in a three-neck flask in a batch process. The concentration variation of NaOH is 10, 15, 20, 25, and 30 (wt.) while experiments were carried out in duration times of 60, 90, 120, 150, and 180 minutes. The operating temperature was set at a temperature of 90 °C. In the delignification process with various concentrations of NaOH solution, the experimental results showed that the correlation between the processing time on the yield and the lignin content produced is initially and directly proportional. The optimum condition occurred when the processing time reached 120 minutes. Increasing the processing time caused a decrease in the yield and the lignin content produced. Over-processing may cause a degradation of dissolved lignin. Based on the optimum processing time result, the concentration of NaOH solution was investigated. The results showed that the optimum concentration of NaOH solution was 20. The results from the FTIR analysis showed that the crude extract powder produced in this study had the wavelength of the constituent functional groups that were matching the standard lignin constituent functional groups. © 2022. The Author('s). All rights reserved.